2D:4D does not predict economic preferences: Evidence from a large, representative sample - Levent Neyse; Magnus Johannesson; Anna Dreber (Journal of Economic Behavior & Organization, 2021)
The digit ratio (2D:4D) is considered a proxy for testosterone exposure in utero, and there has been a recent surge of studies testing whether 2D:4D is associated with economic preferences. Although the results are not conclusive, previous studies have reported statistically significant correlations between 2D:4D and risk taking, altruism, positive reciprocity, negative reciprocity and trust. However, most previous studies have small sample sizes gathered from university students and there is also no consensus on the type of analysis (e.g., which hand to analyze or subgroup to focus on) or the preference elicitation method. We present results from a pre-registered large sample study testing if 2D:4D is associated with economic preferences. Data were collected in a representative sample of adults in the German Socioeconomic Panel-Innovation Sample (SOEP-IS), in a sample of about 3450 respondents (about 5 times larger than the previously largest study in this field). Using experimentally validated survey questions, we find no statistically significant association between 2D:4D and economic preferences in the largest study to this date on the topic.
Keywords: D03; D87; D9; 330; Economic behavior; Prenatal hormones; Testosterone; Digit ratio